2022
DOI: 10.1155/2022/5387795
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Work Environment on Employee’s Psychological Relationship: A Case Study of Japanese Literature

Abstract: The new generation of employees grows up in the environment of rapid economic development, fierce competition, diversified values, and multiple channels of cultural communication, and their unique growth environment creates characteristics such as their unstable psychological state, poor adjustment ability, and significant self-awareness. The special psychological condition of the new generation employees will affect their own development and that of the organization. How to effectively manage the psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The younger generation of employees experiences a distinct developmental environment characterized by rapid economic progress and diverse values, which in turn affects their mental state and adaptability. In the realm of human resource management, it is crucial to effectively manage the PsyCap of these employees (Xin, 2022). According to Kim et al (2021), the innovative behavior of employees is indirectly influenced by their developmental work experience, through the lens of their PsyCap and burnout.…”
Section: Generational Characteristics and Psycapmentioning
confidence: 99%
“…The younger generation of employees experiences a distinct developmental environment characterized by rapid economic progress and diverse values, which in turn affects their mental state and adaptability. In the realm of human resource management, it is crucial to effectively manage the PsyCap of these employees (Xin, 2022). According to Kim et al (2021), the innovative behavior of employees is indirectly influenced by their developmental work experience, through the lens of their PsyCap and burnout.…”
Section: Generational Characteristics and Psycapmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: The presence of these indicators undermines our confidence in the integrity of the article's content and we cannot, therefore, vouch for its reliability.…”
mentioning
confidence: 99%